Low immunogenicity of quadrivalent meningococcal vaccines in solid organ transplant recipients. Issue 2 (6th March 2015) - Wyplosz, B.; Derradji, O.; Hong, E.; François, H.; Durrbach, A.; Duclos‐Vallée, J.‐C.; Samuel, D.; Escaut, L.; Launay, O.; Vittecoq, D.; Taha, M.K.
Abstract: Immunization against meningococcal disease is recommended for solid organ transplant (SOT) recipients at high risk for meningococcal disease or travelling to an endemic country. However, the immunogenicity of meningococcal vaccines has not been studied in this population. We analyzed the immune response of quadrivalent (against Neisseria meningitidis serogroups A, C, Y, and W) polysaccharidic non‐conjugate and conjugate meningococcal vaccines in kidney‐ and liver‐transplant patients using bactericidal assays against the targeted serogroups. Upon vaccination with a non‐conjugate ( n = 5) or a conjugate vaccine ( n = 10), respectively, 40% and 50% of patients were able to mount an immune response, achieving at least the threshold correlated with protection defined as human serum bactericidal antibody titers of ≥4. Responders showed only partial and low responses (titers ≤64), thus predicting a rapid decline in bactericidal response. Only 1 patient developed a booster response to preexisting immunity. Our data argue for the need of additional measures for SOT recipients, when they are at risk of meningococcal disease.